PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN BAAMBOOZLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN MOTIVASI BELAJAR SISWA - Ingke Joanna; Khoirul Anwar (STKIP Subang, 2024)
Students' mathematical problem solving abilities and learning motivation are still very low, which is influenced by learning activities in class. The problem based learning model is a problem based learning model that can train students to express their opinions in solving problems in real learning contexts. This research aims to determine the effect of implementing the problem based learning model assisted by baamboozle on students' mathematical problem solving abilities and learning motivation. The research method used is a mix method or a combination of quantitative and qualitative methods. This research used pre-experimental with 1 experimental class determined based on purposive sampling. The data collection method uses tests, while the data analysis technique uses t-test or paired sample t-test. The research results obtained were a significance value of 0.001 < 0.05 and the t-count results obtained were |-4.323| > ttable |4,183| then the results of the hypothesis test showed that H0 is rejected and Ha is accepted. Thus, it can be seen that the problem based learning model assisted by baamboozle has a significant effect on students' mathematical problem solving abilities and learning motivation.